Prospect and implementation of telemedicine centers in south Asian countries - Jafar, Imran Bin; Shahin, Md Zahidul Islam; Chakraborty, Partha (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2nd International Conference on Electrical Engineering and Information and Communication Technology, iCEEiCT 2015; Jahangirnagar UniversitySavar, Dhaka; Bangladesh; 21 May 2015 through 23 May 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICEEICT.2015.7307441